2023
DOI: 10.3389/fimmu.2023.1279808
|View full text |Cite
|
Sign up to set email alerts
|

Case Report: Telitacicept in treating a patient with NF155+ autoimmune nodopathy: a successful attempt to manage recurrent elevated sero-anti-NF155 antibodies

Yijun Ren,
Si Chen,
Huan Yang

Abstract: This report presents a case of a neurofascin-155 (NF155)+ autoimmune nodopathy (AN) patient who exhibited resistance to conventional treatments but responded positively to telitacicept therapy. Telitacicept, a dual inhibitor of B lymphocyte stimulator (BLyS) and A proliferation-inducing ligand (APRIL), suppressed the development and survival of plasma cells and mature B cells. The patient’s unique clinical features were consistent with NF155+ AN, showing limited response to standard treatments like rituximab a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Telitacicept has been granted orphan drug status of MG by the Food and Drug Administration (FDA) and received its first approval for treating SLE in China [ 36 ]. Our previous research has also reported successful therapy outcomes of telitacicept on neurofascin-155 (NF155) + autoimmune nodopathy [ 37 ]. Further clinical trials of telitacicept on MG are necessary, and a phase 3 clinical trial of telitacicept for generalized AChR + MG therapy is being conducted by our research group.…”
Section: Discussionmentioning
confidence: 99%
“…Telitacicept has been granted orphan drug status of MG by the Food and Drug Administration (FDA) and received its first approval for treating SLE in China [ 36 ]. Our previous research has also reported successful therapy outcomes of telitacicept on neurofascin-155 (NF155) + autoimmune nodopathy [ 37 ]. Further clinical trials of telitacicept on MG are necessary, and a phase 3 clinical trial of telitacicept for generalized AChR + MG therapy is being conducted by our research group.…”
Section: Discussionmentioning
confidence: 99%